Investigation on Inorganic Salts K2TiF6 and KBF4 to Develop Nanoparticles Based TiB2 Reinforcement Aluminium Composites - Vinayagam Mohanavel; K. Ravi Kumar; T. Sathish; Palanivel Velmurugan; Alagar Karthick; M. Ravichandran; Saleh Alfarraj; Hesham S. Almoallim; Shanmugam Sureshkumar; J. Isaac JoshuaRamesh Lalvani (Bioinorganic Chemistry and Applications)
In the current research, AA6082 aluminium alloy matrix composites (AAMCs) incorporated with various weight fractions of titanium diboride (0, 3, 6, and 9 wt%) were prepared via an in situ casting technique. The exothermic reaction between inorganic powders like dipotassium hexafluorotitanate (K2TiF6) and potassium tetrafluoroborate (KBF4) in molten Al metal contributes to the development of titanium diboride content. The manufactured AA6082-TiB2 AAMCs were evaluated using a scanning electron microscope (SEM) and X-ray diffraction (XRD). The mechanical properties and wear rate (WR) of the AAMCs were investigated. XRD guarantees the creation of TiB2 phases and proves the nonappearance of reaction products in the AMCs. SEM studies depict the even dispersion of TiB2 in the matrix alloy. The mechanical and tribological properties (MTP) of the AAMCs showed improvement by the dispersion of TiB2 particles. The WR decreases steadily with TiB2 and the least WR is seen at nine weight concentrations of TiB2/AA6082 AAMCs. Fabricated composites revealed 47.9% higher flexural strength and 14.2% superior compression strength than the base AA6082 alloy.